Gastroprotective and ulcer healing effects of hydroethanolic extract of leaves of Caryocar coriaceum: Mechanisms involved in the gastroprotective activity. (5th January 2017) - de Lacerda Neto, Luis Jardelino; Ramos, Andreza Guedes Barbosa; Santos Sales, Valterlucio; de Souza, Severino Denicio Gonçalves; dos Santos, Antonia Thassya Lucas; de Oliveira, Larissa Rolim; Kerntopf, Marta Regina; de Albuquerque, Thais Rodrigues; Coutinho, Henrique Douglas Melo; Quintans-Júnior, Lucindo Jose; Wanderley, Almir Gonçalves; de Menezes, Irwin Rose Alencar
Abstract: This work aimed to determine the chemical fingerprint of hydroethanolic extract of leaves of Caryocar coriaceum (HELCC) and the gastroprotective activity. The chemical fingerprint of HELCC was analyzed by HPLC-DAD, to quantify total phenols and flavonoids were carried out by Folin-Ciocalteu reagent and aluminum chloride assay, while in vitro antioxidant activity was evaluated by the DPPH method. The methods used to determine pharmacological activity were: gastroprotective screening test in classical models of induced acute and chronic gastric lesions and physical barrier test. Further assays were performed to demonstrate the involvement of NO, prostaglandins, ATP-dependent potassium channels, TRPV, noradrenergic α2 receptors, histamines, and opioids. The DPPH method demonstrated the antioxidant activity of the extract, in vitro, explained by the presence of polyphenols and flavonoids. Oral administration of the extract, previously dissolved in deionized water, at a dose of 100 mg/kg decreased the lesions induced by indomethacin, acidified ethanol, ethanol and acetic acid by 75.0, 72.8, 69.4 and 86.2% respectively. It was demonstrated that opioid receptors, α2 -adrenergic receptors and primary afferent neurons sensitive to capsaicin were involved in the mechanism of gastric protection, in addition to the contribution of NO and prostaglandins. The results show that extract is a promising candidate for the treatment of gastric ulcers. Graphical abstract: Highlights: The HELCC presents polyphenols and flavonoids. Screening of activity of the extract for gastroprotection activity. Elucidations of mechanism of actions for gastroprotection activity. Histological analysis under chronic ulcer effect.